Tradisi Badantam dalam Alek Perkawinan Perspektif ‘Urf (Studi Kasus di Korong Pautan Kabau, Nagari Sunua, Kecamatan Nan Sabaris, Kabupaten Padang Pariaman) - Icha Agustin; Rahmiati (AHKAM, 2026)
Although the badantam tradition has become part of the social and cultural life of the community of Korong Pautan Kabau, Nagari Sunua, studies specifically analyzing its implementation and status from the perspective of ‘urf remain limited. This study aimed to analyze the implementation of the badantam tradition in alek perkawinan and to determine its status from the perspective of ‘urf. This study employed a qualitative approach through field research with a descriptive design. Informants were selected purposively and included the Wali Nagari Sunua, the Kepala Mudo or niniak mamak, the Chair of Bamus Nagari Sunua, and customary leaders familiar with the badantam tradition. Data were collected through interviews, observation, and documentation and were subsequently analyzed descriptively using deductive and inductive reasoning and the perspective of ‘urf. The findings showed that badantam was performed after the marriage contract by involving families, relatives, and community members through contributions of money, gold, goods, and labor. This tradition functions to help finance alek perkawinan while strengthening community solidarity and mutual cooperation. From the perspective of ‘urf, the badantam tradition constitutes ‘urf khāṣṣ based on its scope and is categorized as ‘urf ṣaḥīḥ because it has been accepted and practiced repeatedly and promotes public benefit. This study concludes that the badantam tradition can be maintained as a social mechanism for supporting wedding celebrations and strengthening community solidarity. These findings broaden Islamic law scholarship on local customary practices and affirm the importance of preserving the value of mutual cooperation within this tradition while avoiding social pressure that may harm the community.